2016
DOI: 10.1017/s0261143016000672
|View full text |Cite
|
Sign up to set email alerts
|

Mid-century Modern Jazz: Music and Design in the Postwar Home

Abstract: This article takes an imagined, transnational living room as its setting, examining jazz's place in representations of the 'modern' middle-class home across the post-war West, and exploring the domestic uses that listeners both casual and committed made of the music in recorded form. In magazines as apparently diverse as Ideal Home in the UK and Playboy in the US, a certain kind of jazz helped mark a new middlebrow connoisseurship in the 1950s and 60s. Yet rather than simply locating the style in a historical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…These changes in public and private living spaces make it important to situate record covers in the Swedish living rooms of the 1950s. Tom Perchard (2017) points out that jazz was connected to media that were consumed in the living room, such as the record player. The connection between furniture design and record covers also relates to the equipment that played the music.…”
Section: Visual Culture In Sweden Of the 1950smentioning
confidence: 99%
See 1 more Smart Citation
“…These changes in public and private living spaces make it important to situate record covers in the Swedish living rooms of the 1950s. Tom Perchard (2017) points out that jazz was connected to media that were consumed in the living room, such as the record player. The connection between furniture design and record covers also relates to the equipment that played the music.…”
Section: Visual Culture In Sweden Of the 1950smentioning
confidence: 99%
“…The latter system shows striking similarities to the record stand described earlier. From an international perspective, it is important to note that in Sweden there was no explicit understanding of this kind of furniture as being connected to the ‘Scandinavian design’ that arose abroad (Perchard, 2017). For many Swedes, this furniture was primarily ‘modern’, and generally, ideas of modern ways of living tended to be inspired by the USA if they were at all connected to a nation-state.…”
Section: Visual Culture In Sweden Of the 1950smentioning
confidence: 99%
“…en, it defines the ideal bourgeois family. Jazz album cover art reflects the international modern visual aesthetics [3]. Wu et al found that the unprecedented availability of social media data provides data owners, system operators, solution providers, and end users with numerous opportunities to explore and understand social dynamics.…”
Section: Introductionmentioning
confidence: 99%